Green water in a brown landscape: Soil characteristics and water availability along an aridity gradient in deciduous oak forests of Michoacán, Mexico - Reyna-Pérez, J. Antonio; Lara-De la Cruz, Libny I.; Beltrán-Paz, Ofelia I.; Santini, Nadia S.; Solleiro-Rebolledo, Elizabeth; Chávez-Vergara, Bruno M. (Forest Systems, 2025)
Aim of the study: Green Water at the End of the Dry Season (GWAEDS), refers to the soil water that remains available in the root zone of plants at the end of the dry season, and it is an important soil property that may improve accuracy in models of aridity increment derived from climate change scenarios. This work aims to understand key environmental drivers of soil water availability at the end of the dry season, along a gradient of increasing aridity in the soils of temperate deciduous forests of central-western Mexico.Area of study: The Cuitzeo Basin (19° 30’-20° 05’ N; 100° 35’-101° 30’ W) within the Trans-Mexican Volcanic Belt in west-central Mexico.Material and methods: We quantified the GWAEDS and correlated it with soil physical and chemical properties, bioclimatic variables, and vegetation greenness (assessed as the Enhanced Vegetation Index, EVI) during the dry season across four sites spanning a gradient of increasing aridity in forests with common dominant oak species (Quercus castanea Née) on volcanic soils in central-western Mexico.Main results: We observed differences in GWAEDS content across the four sites. Soil properties such as organic carbon content, horizon thickness, and pore space accounted for around 70% of the available soil water. In contrast, bioclimatic variables and vegetation greenness did not correlate significantly with GWAEDS. Notably, the site with the lowest annual mean precipitation exhibited the highest GWAEDS value, while the site with the second-highest precipitation showed 50% less green water. These findings underscore the buffering capacity of soil properties in regulating water availability.Research highlights:Soil organic carbon, pore space, and horizon thickness explained approximately 70% of the variation in green water content.Edaphic properties derived from heterogeneity in pedogenetic processes regulate the green water in an aridity increment scenario.Soil properties may buffer water availability, with low-precipitation sites showing higher green water storage.